I feel angry : why do I feel angry today? (London Dorling Kindersly Limited, 2020)
We all get angry sometimes. This illustrated board book helps young children understand why they get angry and how to deal with it. I Feel Angry guides children through their emotions with the help of a fun illustrated flame character who often finds themselves getting angry. What can the little flame do when they feel this emotion? Angry feelings are illustrated as real objects such as red mist and an expanding balloon, making it easier for young children to understand what anger is and how they can deal with it. This book also provides helpful tips and tricks to aid children in controlling their anger that they can practise by themselves
Linguistic notions
2
Keywords: Anger -- Juvenile fiction; Anger; board books